2017
DOI: 10.26836/ijasrd/2017/v4/i7/4706
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Work Place Stress on Well-being of Nursing Staff

Abstract: Stress at workplace is a growing concern in organisations which needs to be addressed. Employees face conditions of excessive pressure, heavy workload, job insecurity, low levels of job satisfaction, internal conflicts and lack of autonomy. Previous studies show that workplace stress has detrimental effect on the health and well-being of employees, as well as a negative impact on organisations results. However, employees first need to recognize the symptoms that indicate they are feeling stressed out, and empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The study carried out by Rani and Thyagarajan [ 14 ] was in line with present study findings, which reported that most nurses complained of a heavy workload, which is considered the primary contributing factor for work-related stress. Similarly, results from the study performed by Godwin et al [ 15 ] reinforced the proposition that nurses experienced an above-average level of work-related stress.…”
Section: Discussionsupporting
confidence: 91%
“…The study carried out by Rani and Thyagarajan [ 14 ] was in line with present study findings, which reported that most nurses complained of a heavy workload, which is considered the primary contributing factor for work-related stress. Similarly, results from the study performed by Godwin et al [ 15 ] reinforced the proposition that nurses experienced an above-average level of work-related stress.…”
Section: Discussionsupporting
confidence: 91%